Inhibition of xyloglucanase from an alkalothermophilic thermomonospora sp by a peptidic aspartic protease inhibitor from Penicillium sp VM24 - Menon, Vishnu; Rao, Mala (Bioresource Technology, 2012)
A bifunctional inhibitor from Penicilliurn sp VM24 causing inactivation of xyloglucanase from Thermomonospora sp and an aspartic protease from Aspergillus saitoi was identified. Steady state kinetics studies of xyloglucanase and the inhibitor revealed an irreversible, non-competitive, two-step inhibition mechanism with IC50 and K-i; values of 780 and 500 nM respectively. The interaction of o-phthalaldehyde (OPTA)-labeled xyloglucanase with the inhibitor revealed that the inhibitor binds to the active site of the enzyme. Far- and near-UV spectrophotometric analysis suggests that the conformational changes induced in xyloglucanase by the inhibitor may be due to irreversible denaturation of enzyme. The bifunctional inhibitor may have potential as a biocontrol agent for the protection of plants against phytopathogenic fungi. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aspartic protease; Bifunctional inhibitor; Biocontrol agent; Inactivation mechanism; Xyloglucanase